Isolation, Characterization, and Multipotent Differentiation of Mesenchymal Stem Cells Derived from Meniscal Debris - Weili Fu; Xing Xie; Qi Li; Gang Chen; Chenghao Zhang; Xin Tang; Jian Li (Hindawi Limited, 2016)
This study aimed to culture and characterize mesenchymal stem cells derived from meniscal debris. Cells in meniscal debris from patients with meniscal injury were isolated by enzymatic digestion, cultured in vitro to the third passage, and analyzed by light microscopy to observe morphology and growth. Third-passage cultures were also analyzed for immunophenotype and ability to differentiate into osteogenic, adipogenic, and chondrogenic lineages. After 4-5 days in culture, cells showed a long fusiform shape and adhered to the plastic walls. After 10-12 days, cell clusters and colonies were observed. Third-passage cells showed uniform morphology and good proliferation. They expressed CD44, CD90, and CD105 but were negative for CD34 and CD45. Cultures induced to differentiate via osteogenesis became positive for Alizarin Red staining as well as alkaline phosphatase activity. Cultures induced to undergo adipogenesis were positive for Oil Red O staining. Cultures induced to undergo chondrogenesis were positive for staining with Toluidine Blue, Alcian Blue, and type II collagen immunohistochemistry, indicating cartilage-specific matrix. These results indicate that the cells we cultured from meniscal debris are mesenchymal stem cells capable of differentiating along three lineages. These stem cells may be valuable source for meniscal regeneration.